Pengaruh Disiplin Kerja dan Kompensasi Kerja Terhadap Produktivitas Kerja Karyawan di SMKN 1 Gunung Putri Bogor - Muhamad Fikri Fadilah; Muhamad Azis Firdaus; Agung Wibowo (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of Work Discipline (X1) and Work Compensation (X2) on Work Productivity (Y). Researchers conducted research at SMKN 1 Gunung Putri Bogor. The population amounted to 60 employees. The sampling technique used saturated sampling and a sample of 60 employees was used. The data analysis technique used is statistical test analysis, namely Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, Hypothesis Test (t), Hypothesis Test (f), and Coefficient of Determination Test using the help of the SPSS version 26 application. Based on the results of the tests carried out, it can be concluded that both partially and simultaneously Work Discipline (X1) and Work Compensation (X2) have a significant influence on Employee Productivity (Y) at SMKN 1 Gunug Putri Bogor.